2014
DOI: 10.1038/srep03745
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Three Novel Mutations in the FRMD7 Gene for X-linked Idiopathic Congenital Nystagmus

Abstract: Idiopathic congenital nystagmus (ICN) consists of involuntary and periodic ocular motility, often with seriously reduced visual acuity. To identify the genetic defects associated with X-linked ICN, we performed PCR-based DNA direct sequencing of two candidate genes, FRMD7 and GPR143, in four families. Mutation analysis led to identification of three novel mutations, p.S260R, p.Q487X, and p.V549Y fsX554, in FRMD7 in three of the recruited families. Results from structural modeling indicated that the p.S260R may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Mutations of FRMD7 are the major etiological contributor of ICN (1)(2)(3)(4)(5). A previous study by the current authors demonstrated that FRMD7 interacts with RhoGDI, whereby it specifically activates the Rac1 signalling involved in neuronal development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations of FRMD7 are the major etiological contributor of ICN (1)(2)(3)(4)(5). A previous study by the current authors demonstrated that FRMD7 interacts with RhoGDI, whereby it specifically activates the Rac1 signalling involved in neuronal development.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no effective treatments for ICN and patients experience a significant decrease in their quality of life over time. To date, >40 mutations of FRMD7 have been detected worldwide in people from various ethnic backgrounds (1)(2)(3)(4)(5)(7)(8)(9). A previous study by the current authors identified two novel missense mutations (c.781C>G and c.886G>C) and a truncated mutation (c.1003C>T) of human FRMD7 in three X-linked ICN pedigrees (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The most common cause of congenital nystagmus seems to be mutations of the X-linked FRMD7 gene (NYS1), which also have been detected by us and others in China. 4 Mutations in the GPR143 gene have been found to be responsible for another X-linked ocular albinism and nystagmus (NYS6). Moreover, at least six susceptibility loci have been mapped from 1996 to 2014, including NYS2 (6p12; OMIM 164100), NYS3 (7p11; OMIM 608345), NYS4 (13q; OMIM 193003), NYS5 (Xp11.4; OMIM 300589), NYS7 (1q31-q32; OMIM 614826), and one additional locus in the X chromosome identified by a recent study.…”
Section: Introductionmentioning
confidence: 99%
“…6 Identification of disease-causing mutations will provide a basis for determining the molecular pathogenesis of the disease and for the development of effective therapies. To identify potential genetic etiology for these ocular disorders in our hereditary disease program, 4 we applied whole-exome sequencing (WES) and bioinformatics to recently recruited patients with nystagmus. In this study we report both the identification of heterozygous mutations in the MANBA gene in patients with infantile nystagmus and the molecular association of nystagmus with lysosomal storage disease (LSDs).…”
Section: Introductionmentioning
confidence: 99%